2014
DOI: 10.3741/jkwra.2014.47.10.945
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Spatio-Temporal Distributions of Winter Soil Temperature Taking Account of Snow-melting and Soil Freezing-Thawing Processes

Abstract: Soil temperature is one of the most important environmental factors that govern hydrological and biogeochemical processes related to diffuse pollution. In this study, considering the snowmelting and the soil freezing-thawing processes, a set of computer codes to estimate winter soil temperature has been developed for CAMEL (Chemicals, Agricultural Management and Erosion Losses), a distributed watershed model. The model was calibrated and validated against the field measurements for three months at 4 sites acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Jennings et al (2018) found that rain-snow Tair thresholds exhibited significant spatial variability across the Northern Hemisphere with the warmest thresholds in continental and mountain areas while with the coolest thresholds in maritime areas and lowlands. This implies that the high Tair threshold (i.e., 2.5℃) used in Noah-MP may lead to the overestimated snowfall, and subsequently the overestimated snow depth and SWE as the study area is characterized by Simplified snow layering schemes (i.e., single snow layer) with the assumption of the same snow density for the entire snow column cause rapid snowmelt (e.g., Kwon et al, 2014;Suzuki and Zupanski, 2018). Although the snowpack in Noah-MP can have up to three snow layers, it may not be enough to accurately reproduce the energy budget within the snowpack in the study area.…”
Section: Limitationsmentioning
confidence: 99%
“…Jennings et al (2018) found that rain-snow Tair thresholds exhibited significant spatial variability across the Northern Hemisphere with the warmest thresholds in continental and mountain areas while with the coolest thresholds in maritime areas and lowlands. This implies that the high Tair threshold (i.e., 2.5℃) used in Noah-MP may lead to the overestimated snowfall, and subsequently the overestimated snow depth and SWE as the study area is characterized by Simplified snow layering schemes (i.e., single snow layer) with the assumption of the same snow density for the entire snow column cause rapid snowmelt (e.g., Kwon et al, 2014;Suzuki and Zupanski, 2018). Although the snowpack in Noah-MP can have up to three snow layers, it may not be enough to accurately reproduce the energy budget within the snowpack in the study area.…”
Section: Limitationsmentioning
confidence: 99%